Akselerasi Kemampuan Membaca Turost Santri Melalui Metode Al-Misbah: Melalui Metode Al-Misbah: (Studi Kasus di Pondok Pesantren Modern Al-Amanah Krian-Sidoarjo) - Najib, M. Miftahun; Hidayat.HS, Dafid Fajar (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2024)
The yellow book or turost has an important role in Islamic learning in Islamic boarding schools, especially to deepen classical sciences. Modern Islamic boarding schools, which have a shorter learning system, often experience challenges in teaching nahwu and shorof sciences in depth to their students. As a result, students often do not have an adequate understanding of turost. This study examines the effectiveness of the Al-Misbah method in accelerating the ability to read turost in students at the Al-Amanah Krian Modern Islamic Boarding School, Sidoarjo. The main focus of this study is to improve students' understanding of the yellow book with a more practical and visual approach, considering the limited time they spend studying in modern Islamic boarding schools. The Al-Misbah method is presented as an alternative that emphasizes direct practice and visualization, which is expected to make it easier for Generation Z students to understand turost without having to go through a long process of mastering nahwu and shorof. The research approach used is a qualitative method with interview techniques, observation, and field data analysis. The results of the study showed that the Al-Misbah method was able to significantly improve the reading ability of students at the Al-Amanah Krian Modern Islamic Boarding School in a shorter time compared to traditional methods. As many as 85% of students involved in this study experienced an increase in their understanding of the text independently, while 72% felt that this method was more interesting and suited to their learning style. This method also supports the learning characteristics of generation Z, which is more responsive to visual media and direct practice than memorizing long grammar rules. Thus, the Al-Misbah method can be used as an effective turost learning method for modern Islamic boarding schools, which allows students to gain a deep understanding of the yellow book even in limited study time.